2019
DOI: 10.5005/jp-journals-10071-23108
|View full text |Cite
|
Sign up to set email alerts
|

Time to Detection of Yeast Isolates in Pediatric and Adult Patients with Fungemia and its Relevance to Clinical Profile and Outcome

Abstract: Context Time to detection (TTD) given by continuous monitoring automated blood culture systems (CMABS) have been found to be a predictor of clinical outcome, drug resistance and type of microorganism in cases of bacteremia but the studies evaluating TTD with respect to fungemia are scarce especially from India. Aims To evaluate TTD for yeast isolates in fungal bloodstream infections with respect to the type of yeast isolates, risk factors and outcome and to study yeast … Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
2

Citation Types

2
5
0

Year Published

2021
2021
2024
2024

Publication Types

Select...
4

Relationship

0
4

Authors

Journals

citations
Cited by 4 publications
(7 citation statements)
references
References 16 publications
2
5
0
Order By: Relevance
“…Study conducted by Park et al reported mean TTP of C. glabrata, C. albicans, C. parapsilosis and C. tropicalis to be 50.8 hrs, 37.5 hrs, 35.3 hrs and 22.4 hrs respectively ( 21 ). Study conducted in India by Butta et al also reported that TTP of C. tropicalis and C. glabrata was found to be significantly shorter and longer respectively when compared to other isolates ( 22 ). The findings in our study as well as those in other studies suggest that while TTP differs among different species of Candida , shorter TTP may be predictive of candidemia caused by C. tropicalis and longer TTP maybe predictive of candidemia caused by C. glabrata.…”
Section: Discussionmentioning
confidence: 98%
“…Study conducted by Park et al reported mean TTP of C. glabrata, C. albicans, C. parapsilosis and C. tropicalis to be 50.8 hrs, 37.5 hrs, 35.3 hrs and 22.4 hrs respectively ( 21 ). Study conducted in India by Butta et al also reported that TTP of C. tropicalis and C. glabrata was found to be significantly shorter and longer respectively when compared to other isolates ( 22 ). The findings in our study as well as those in other studies suggest that while TTP differs among different species of Candida , shorter TTP may be predictive of candidemia caused by C. tropicalis and longer TTP maybe predictive of candidemia caused by C. glabrata.…”
Section: Discussionmentioning
confidence: 98%
“…might also cause IFIs (Kotey et al, 2021). Early detection and treatment have proven to have crucial role for prognosis, especially in guidance of antifungal stewardship committees (Butta et al, 2019;Dudakova, 2022). However, indirect diagnostic procedures (serology, etc.)…”
Section: Discussionmentioning
confidence: 99%
“…In turn, in single-center Swedish studies, C. albicans constituted as much as 65.0% of isolated Candida fungi [29]. However, the participation of individual species may vary depending on the patient group and institution [5,9,30,31].…”
Section: Discussionmentioning
confidence: 99%